Nervous system involvement in Hodgkin's disease patients at Marmara University Hospital between 1989 and 1995 - (:unkn) unknown (My University, 1997)
Objective: Nervous System involvement in Hodgkin's disease is a very uncommon occurrence at presentation and during the course of the disease. This paper analyzes the incidence and the clinical manifestations of nervous system involvement of all cases of Hodgkin's disease seen at Marmara University Hospital. Methods: The records of all cases of Hodgkin's Disease patients seen at Marmara University Hospital, were examined to determine whether nervous system involvement had occurred at any time during the course of the disease between 1989 and 1995. Results: Neurologic complications were observed in four of 23 total cases in our series of Hodgkin's Disease, giving an overall incidence of 17%. All four patients presented with neurological findings had evidence of advanced disease at presentation with B symptoms. Two of the patients had clinical paraneoplastic syndrome and the other two were determined to have paraspinal masses. Conclusion: These figures represented here probably do not reflect the true incidence in the country, since Marmara University Hospital is a reference hospital in Istanbul and those patients with advanced disease or patients at a later stage of their disease are referred to our Hematology Department.
Keywords: Hodgkin's disease; Nervous system